Robust Antibody Levels in Both Diabetic and Non-Diabetic Individuals After BNT162b2 mRNA COVID-19 Vaccination - Ali, Hamad; Alterki, Abdulmohsen; Sindhu, Sardar; Alahmad, Barrak; Hammad, Maha; Al-Sabah, Salman; Alghounaim, Mohammad; Jamal, Mohammad H.; Aldei, Ali; Mairza, Mohammad J.; Husain, Maitham; Deverajan, Sriraman; et al. (Frontiers in Immunology, 2021)
The emergence of effective vaccines for COVID-19 has been welcomed by the world with great optimism. Given their increased susceptibility to COVID-19, the question arises whether individuals with type-2 diabetes mellitus (T2DM) and other metabolic conditions can respond effectively to the mRNA-based vaccine. We aimed to evaluate the levels of anti-SARS-CoV-2 IgG and neutralizing antibodies in people with T2DM and/or other metabolic risk factors (hypertension and obesity) compared to those without. This study included 262 people (81 diabetic and 181 non-diabetic persons) that took two doses of BNT162b2 (Pfizer–BioNTech) mRNA vaccine. Both T2DM and non-diabetic individuals had a robust response to vaccination as demonstrated by their high antibody titers. However, both SARS-CoV-2 IgG and neutralizing antibodies titers were lower in people with T2DM. The mean (±1 standard deviation) levels were 154±49.1 vs. 138±59.4BAU/mL for IgG and 87.1±11.6 vs. 79.7±19.5% for neutralizing antibodies in individuals without diabetes compared to those with T2DM, respectively. In a multiple linear regression adjusted for individual characteristics, comorbidities, previous COVID-19 infection and duration since second vaccine dose, diabetics had 13.86 BAU/ml (95%CI: 27.08 to 0.64BAU/ml, p=0.041) less IgG antibodies and 4.42% (95%CI: 8.53 to 0.32%, p=0.036) fewer neutralizing antibodies than non-diabetics. Hypertension and obesity did not show significant changes in antibody titers. Taken together, both type-2 diabetic and non-diabetic individuals elicited strong immune responses to SARS-CoV-2 BNT162b2 mRNA vaccine; nonetheless, lower levels were seen in people with diabetes. Continuous monitoring of the antibody levels might be a good indicator to guide personalized needs for further booster shots to maintain adaptive immunity, nonetheless, it’s important that people get their COVID19 vaccination especially people with diabetes.